2011
DOI: 10.1007/s13139-010-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of F-18 FDG PET/CT in Assessment of Recurrence of Cervical Cancer After Treatment

Abstract: As F-18 FDG PET/CT has high sensitivity and negative predictive value in diagnosis of recurrent cervical cancers, it is expected that it will be useful for clinical determination of recurrence and prevention of unnecessary additional treatments. The hope is that a future study on a larger scale will contribute further to determination of the efficacy of PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Up to now, the clinical use of FDG PET/CT has been established in gynecological malignancies such as cervical, ovarian, and vulvar cancer. However, only a few studies [20,21] have reported the prognostic value of FDG PET/CT in gynecological malignancies. To the best of our knowledge, this is the second report regarding the prognostic value of FDG PET/CT by semiquantitatively measuring the SUVmax of primary tumors and LNs in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the clinical use of FDG PET/CT has been established in gynecological malignancies such as cervical, ovarian, and vulvar cancer. However, only a few studies [20,21] have reported the prognostic value of FDG PET/CT in gynecological malignancies. To the best of our knowledge, this is the second report regarding the prognostic value of FDG PET/CT by semiquantitatively measuring the SUVmax of primary tumors and LNs in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al studied 51 patients with treated cervical cancer and found tumor recurrence or metastasis in 37. They found PET/CT to have a sensitivity of 97.3%, a specificity of 71.4%, and an accuracy of 90.2%[39]. PET/CT has been shown to detect metastases in asymptomatic patients and in patients with increasing tumor markers.…”
Section: Follow-up Evaluationmentioning
confidence: 99%
“…Does PET/CT improve the accuracy of diagnosis of recurrence compared to CT or MRI in cervical cancer? Statistical analysis for the diagnostic accuracy of CT, MRI, and PET/CT has not been performed due to heterogeneity of the statistical analysis from each studie [ 68 69 70 71 ]. From the review of each study, PET/CT could be used to identify the recurrence of cervical cancer when recurrence is not identified or recurrence is suspicious with conventional image.…”
Section: Clinical Considerations and Recommendationsmentioning
confidence: 99%